Análise epidemiológica, temporal e espacial da esporotricose humana e felina no município de contagem (mg) entre 2017 a 2023 - Ailton Junior Antunes da Costa (2023)
Sporotrichosis, a fungal disease caused by Sporothrix sp., impacts both the human and animal population on a global scale, showing a notable increase in incidence, especially in Brazil since the 1980s. This phenomenon has stimulated a growing interest in the epidemiological investigation of the disease. Understanding the spatio-temporal and social patterns of sporotrichosis is essential to formulate effective prevention and control strategies. In this study, several aspects of the epidemiology of sporotrichosis in humans and animals were addressed, using advanced spatial and temporal analysis techniques. The main objective was to enrich the current knowledge about the epidemiology of the disease, providing crucial perspectives for the development of more effective prevention and control approaches. The results encompassed the epidemiological characterization in human and feline populations, georeferenced mapping and temporal analysis of cases in Contagem, Minas Gerais, from January 2017 to March 2023. The epidemiological data were taken from SINAN and UVZ, which was fundamental in understanding and controlling sporotrichosis in humans and felines over time. This approach included detailed information such as age, sex, and relevant risk factors, as well as classifying cases based on person, time and place, enabling a comprehensive analysis. The temporal analysis revealed trends and seasonality that facilitated the understanding of disease patterns. The use of a geographic information system (GIS) to map cases helped identify areas with higher incidence, which could guide control strategies. Furthermore, statistical analyses, including prevalence, mortality, and lethality rates, as well as regression analyzes to identify risk factors, contribute to supporting effective prevention and control measures. Therefore, the combination of epidemiological studies, spatial and temporal analysis and mathematical modeling is valuable to support a deep understanding of sporotrichosis and its transmission dynamics. It is believed that this work will significantly contribute to expanding scientific knowledge about the disease and to the development of integrated approaches aimed at effective prevention and control.